2015
DOI: 10.5530/ijper.49.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Waste Management in Pharmacies at the Primary Level of Health Care in Serbia - Situation Analysis

Abstract: Background: Pharmaceutical products can become a potential source of poisoning. The improper disposal of unused medicines is a growing problem throughout the world, with a manifold effect on the cost of health care, public health and the environment. The objectives of this research are the overview of current situation of pharmaceutical waste management in the pharmacy sector in the Republic of Serbia, attitudes and knowledge of pharmacists on the matter and the measures they should undertake in order to make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
5
0
3
Order By: Relevance
“…A nationwide study by Bungau et al (2018) with a group of 521 pharmacists, showed that 16% of the participants work for pharmacies that do not collect unused or expired drugs from the people; and nearly 33% of those surveyed have refused, at least once, to take unused medicines from people when asked (Bungau et al 2018). However, according to another study carried out in the Republic of Serbia, in March 2013, 76.5% of pharmacies collect expired medicines that people bring to them, in order to get them put away, while 23.5% of the pharmacies surveyed assert that they do not collect pharmaceutical waste from households at all (Manojlović et al 2015)…”
Section: Resultsmentioning
confidence: 99%
“…A nationwide study by Bungau et al (2018) with a group of 521 pharmacists, showed that 16% of the participants work for pharmacies that do not collect unused or expired drugs from the people; and nearly 33% of those surveyed have refused, at least once, to take unused medicines from people when asked (Bungau et al 2018). However, according to another study carried out in the Republic of Serbia, in March 2013, 76.5% of pharmacies collect expired medicines that people bring to them, in order to get them put away, while 23.5% of the pharmacies surveyed assert that they do not collect pharmaceutical waste from households at all (Manojlović et al 2015)…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a standardized, 20-items, self-administered questionnaire designed and developed to evaluate pharmacist knowledge when generating pharmaceutical waste in pharmacies. The questionnaire was developed depending on information drawn from the literature, and a number of questions were adapted and modified from other studies regarding pharmacist knowledge on drug disposal and its effect on health and environment [1,12,13,14,15,16,17,18]. Validation was performed to determine whether the study tool measured the intended goal of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Manojlović et al (2015), on the opposite side, focus the potential source of poisoning by drugs, due to improper disposal of unused medicines worldwide. They researched pharmacies to assess the current situation of pharmaceutical WM in the sector and results demonstrate that pharmacies have not started to implement their legal obligation of collecting pharmaceutical waste from the citizens yet, at least not in the full range.…”
Section: Resultsmentioning
confidence: 99%